Prevalence and Risk Factors for Anemia in a Population With Hidradenitis Suppurativa - Resnik, Sydney R (Cureus, 2020)
Background: Hidradenitis suppurativa (HS) is an inflammatory disease presenting as nodules evolving into scarred plaques. HS is associated with many co-morbidities, including anemia of chronic disease, though few studies report on this association. Objectives: This study evaluated the prevalence of anemia among the HS patient population and potential associations between risk factors for HS and anemia development. Methods: Records diagnosed HS patients in one private practice (BR) were reviewed by investigators. The 92-patient cohort was evaluated for multiple data-points and responses grouped based on age, gender, ethnicity, body mass index (BMI), smoking status, and comorbidities. Data were analyzed using STATA to perform descriptive analysis and bivariate analysis. Results: The prevalence of anemia in this cohort was 41.3%. Of anemic patients, the majority were men (65.2%), African American (60.6%), and never/former smokers (48.6%). There was a significant increase in the odds of developing anemia in HS patients that are men (odds ratio (OR) 3.8) and African American (OR 3.5). Conclusions: We show that the prevalence of anemia in an HS patient population greatly surpasses that of the U.S. population (~5%). It is clear that anemia is a significant complication for HS patients. We hope that physicians can recognize the importance of screening patients with HS for anemia to medically optimize treatment for their patients.